Progressive Resistance Training Improves Bradykinesia, Motor Symptoms and Functional Performance in Patients with Parkinson’s Disease - Vieira de Moraes Filho A (Dove Medical Press, 2020)
Ariel Vieira de Moraes Filho, 1 Sandro Nobre Chaves, 2, 3 Wagner Rodrigues Martins, 4 Grassyara Pinho Tolentino, 2 Rita de Cássia Pereira Pinto Homem, 2 Gleyverton Landim de Farias, 2 Bruno Leonardo Fischer, 2 Juliene Azevedo Oliveira, 1 Samantha Kênia Abreu Pereira, 1 Samuel Estevam Vidal, 2 Márcio Rabelo Mota, 5 Ricardo Moreno Lima, 2 Ricardo Jacó de Oliveira 1, 2 1College of Health Sciences, University of Brasilia, Brasilia, Brazil; 2College of Physical Education, University of Brasilia, Brasilia, Brazil; 3Integrated Colleges IESGO, Formosa, Goias, Brazil; 4College of Physical Therapy, University of Brasilia, Brasilia, Brazil; 5University Center of Brasilia, Brasilia, BrazilCorrespondence: Sandro Nobre ChavesCollege of Physical Education, University of Brasilia, University Campus Darcy Ribeiro, Brasilia CEP: 70904-970, DF, BrazilTel +55 61 99178 5524Fax +55 61 3107 2500Email sandronobrec@gmail.comPurpose: Bradykinesia and muscle weaknesses are common symptoms of Parkinson’s Disease (PD) and are associated with impaired functional performance, increased risk of falls, and reduced quality of life. Recent studies have pointed to progressive resistance training (PRT) as an effective method to control and reduce these symptoms, increasing possibilities to treat the disease. However, few studies have focused on assessing the PRT effects in the short-term. Therefore, the present study aimed to assess the short-term PRT effects on people with PD, in order to offer new parameters for a better understanding of its effects, so as an adequation and PRT use as a complementary therapy.Patients and Methods: Forty individuals diagnosed with PD from stage 1 to 3 on the Hoehn and Yahr scale took part on the study and were allocated into 2 groups; Training Group (TG) performed a 9-week RT program twice a week, and the Control Group (CG) attended disease lectures. Bradykinesia UPDRS subscale (BSS), knee extensors isokinetic strength, Ten Meters Walk Test (TMW), Timed Up&Go Test (TUG) and 30-Second Chair Stand (T30) were measured before and after the intervention period. Statistical significance was set at p ≤ 0.05.Results: Significant time was noted by the group interaction for all functional tests (TUG, T30, and TWM; all p < 0.01) and BSS (p < 0.01). Post hoc analyses revealed that these differences were driven by significant improvements in these dependent variables (all p < 0.01) while the CG remained unchanged (all p > 0.05). Moreover, TUG, T30, TWM, and BSS were significantly different between TG and CG in the post-training assessments (all p < 0.01). Isokinetic muscle strength was slightly increased in the TG (2.4%) and decreased in the CG (− 2.2%), but statistical analyses did not reach significance for interaction but only a trend (p = 0.12).Conclusion: The results indicate that 9 weeks of PRT reduces bradykinesia and improves functional performance in patients with mild to moderate PD. These findings reinforce this mode of exercise as an important component of public health promotion programs for PD.Keywords: Parkinson disease, physical exercise, resistance training, substantia nigra